Rethinking Reform in the Latin West, 10th to Early 12th Century
1 online resource (368 pages)
Keywords: This collection of studies investigates how people of the 10th to early 12th century experienced and represented processes of intentional change in the Church, and what the consequences are of modern scholars’ reliance on ‘reform’ to describe and interpret these processes. In 11 thematic chapters it takes stock of the current state of research and offers suggestions to deepen our understanding of the ideological, institutional, and cultural dynamics at play. Contributors are Julia Barrow, Robert F. Berkhofer III, Gordon Blennemann, Katy Cubitt, Nicolangelo D'Acunto, Anne-Marie Helvétius, Ludger Körntgen, Rutger Kramer, Brigitte Meijns, Diane Reilly, Rachel Stone, and Steven Vanderputten.